An Andragogical Approach to Teaching Leadership. (December 2017) - McCauley, Kelly Davis; Hammer, Emily; Hinojosa, Amanda S.
Students in today's college classroom are diverse in age and work, leadership, and life experiences; hence, students transitioning into adulthood may understand and relate core leadership knowledge to their own experiences differently than mature adults. As such, we call upon andragogy, a theory of adult learning, to inform our approach to teaching leadership. We employ andragogy and its six assumptions (the learners' self-concept, the role of experience, readiness to learn, orientation to learning, motivation, and the need to know) as a guiding framework for the selection and development of leadership instructional tools, thus creating an individualized learning experience for emerging and full-fledged adults that bridges the leadership theory and practice gap. We offer examples of leadership instructional tools that align with andragogical assumptions and provide suggestions for scaling these assignments and activities to address students' learning needs at different stages of adulthood.